Arthroscopic Extensor Carpi Radialis Brevis Tenotomy and Debridement Versus Debridement Alone for Refractory Lateral Epicondylitis: Clinical and MRI Evaluation. Issue 8 (5th August 2022) - Li, Hong; Yang, Xiang Dong; Xue, XiaoAo; Zhang, Qingguo; Ye, Lingchao; Hua, Yinghui; Zhou, Xiaobo
Background: Arthroscopic debridement of the extensor carpi radialis brevis (ECRB) tendon is a widely accepted procedure used in refractory lateral epicondylitis. However, residual pain occurs in some patients. Purpose: To investigate the clinical effectiveness of arthroscopic extended debridement (ECRB tenotomy and debridement) in the treatment of lateral epicondylitis. Study Design: Cohort study; Level of evidence, 3. Methods: Patients with refractory lateral epicondylitis were consecutively recruited for this study. They underwent traditional ECRB debridement (control group) or extended ECRB debridement (ED group) under arthroscopy. The Disabilities of the Arm, Shoulder and Hand (DASH) score, visual analog scale (VAS) for pain, and Mayo Elbow Performance Score (MEPS) were used to compare elbow function between the groups at 3, 6, and 12 months postoperatively. Magnetic resonance imaging (MRI) was also performed to evaluate pathology at 12 months. Results: A total of 69 patients participated in the study (33 patients in the ED group and 36 in the control group). After surgery, all patients showed improvement on all 3 outcome scores. Compared with the control group, the ED group had significantly better postoperative MEPS and VAS scores at 3 months ( P ≤ .001 for both) and 6 months ( P ≤ .03 for both) but similar values at 12 months. DASH scores between groups were similar at all time periods. At the 12-month follow-up, no patients in the ED group reported pain with strenuous work. Return-to-work (RTW) times were also shorter in the ED group compared with the controls (8 ± 4 vs 18 ± 8 weeks; P < .001). Postoperative MRI assessments revealed no high signal intensities on the lateral epicondyle in the ED group, while there was an increased internal signal intensity on the lateral epicondyle in 83% of the controls. Conclusion: Collectively, the extended ECRB debridement technique resulted in enhanced pain relief in the early postoperative period as well as providing faster RTW times compared with the traditional debridement technique. At 1 year follow-up, there were no differences in outcome measures between groups, but residual abnormal MRI findings were more common in the traditional debridement group.